PERSEPSI PEMUSTAKA TERHADAP KOLEKSI DIGITAL DI UPT PERPUSTAKAAN UNIVERSITAS NEGERI PADANG - Mutiara, Erika; Asmara, Rini (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to analyze user perceptions of digital collections at the Padang State University Library. Using Fred Davis' Technology Acceptance Model (TAM) as a theoretical basis, this study focuses on six key indicators: usefulness, ease of use, social influence, trust, facilitating conditions, and intention to use. The method used was descriptive quantitative, with 100 respondents selected through random sampling. The results indicate that user perceptions of digital collections are generally good across all indicators, particularly in the aspects of usefulness and trust. However, some users still experience obstacles in access and navigation. This study concludes that improving user literacy and digital infrastructure can strengthen the effectiveness of digital collections in supporting academic activities.